Fertilization effects on the growth of common carp (Cyprinus carpio) and Nile tilapia (Oreochromis niloticus) and rice yields in an integrated rice-fish farming system - Billah, Md Masum; Uddin, Md K.; Samad, Mohd Y. A.; Hassan, Mohd Z. B.; Anwar, Md Parvez; Mustafa Kamal, Abu Hena; Shahjahan, M.; Al-Asif, Abdulla (Bioflux, 2019)
An investigation was accompanied in the rice field plots with developing an infrastructure of 30 m2 to ascertain the felicitous fertilization effects of the Nile tilapia (Oreochromis niloticus) and the common carp (Cyrpinus carpio) cultured along with the rice fish farming system in the plots. There were setting up three systems to assess the effect of fish species on tiller yield, regarding for fish species i.e. no fish stocking with rice (C), O. niloticus with rice (FT) and C. carpio with rice (FC). Each treatment of fish species cultured with different doses of fertilizer such as (T0) control: without any fertilization; (T1) with 100% recommended fertilizer (RF); (T2) with 75% recommended fertilizer (RF); (T3) with 10 ton compost fertilizer; (T4) with 5 ton compost fertilizer+75% RF, and rice culture with 5 ton compost fertilizer+50% RF. The maximum number of plant in the tiller were found in C. carpio (FC) species (7.02 no/tiller and 82.95 cm/tiller) whereas lowest in FT (6.40 no/tiller and 81.65 cm/tiller) during 75 DAT. In regards of fertilizer application, the highest values were observed in FC with an average of 31.71, 53.28 and 73.06 cm/tiller during 30, 40 and 60 DAT respectively, followed by F0 (31.92, 52.43 and 72.31 cm/tiller at 30, 45 and 60 DAT) and FT (30.28, 49.76 and 67.25 cm/tiller at 30, 45 and 60 DAT) respectively, in which there was found negative significant differences (P>0.05) among different treatments. The rice production in C. carpio fertilizer treatment T4 (7.30±1.86 kg/m2) was significantly higher than those of other treatments (7.16±2.78, 6.83±2.88, 6.67±1.44, 6.17±1.84 and 4.06±1.76 kg/m2 in treatments T5, T3, T2, T1, and T0 respectively). The yields of fish were significantly higher (P<0.05) in treatments T4, (11.70±3.86 kg/m2) than other fertilizer treatments T5 (11.25±3.56 kg/m2), T3 (10.85±5.76 kg/m2), T2 (10.80±5.55 kg/m2), T1 (9.90±4.66 kg/m2), T0 (4.78±3.48 kg/m2) and in FC and also compared to all other fertilizer treatments in FT. In regards of straw, the yields were significantly higher (P<0.05) in treatments T4, (13.76±6.24 kg/m2) and followed by T5 (13.55±4.42 kg/m2), T3 (12.88±6.24 kg/m2), T2 (10.75±4.65 kg/m2), T1 (10.65±3.36 kg/m2), T0 (4.28±3.86 kg/m2) and in FC and also compared to all other fertilizer treatments in FT. The outcome in T4 provided the maximum yields amongst all treatments, followed by treatments T5, T3, T2, T1 and T0 representing that the amalgamation of basal fertilization and compost fertilizer are the furthermost suitable nutrient input regime aimed at the rice-carpi fish integrated culture scheme.